POLA ASUH NENEK DALAM KELUARGA DI DESA RAMBAH HILIR TENGAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Linda Wati; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Village of Rambah Hilir Tengah Sub-district of Rokan Hulu Regency. The purpose of this research on the influence of parenting in family at Village of Rambah Hilir Tengah Sub-district of Rokan Hulu Regency. Topic focus of this research is the foster pattern Granny uses at Village of Rambah Hilir Tengah Sub-district of Rokan Hulu Regency. The samples in this study amounted to 5 people. The authors use qualitative methods and use purposive sampling techniques. Data instruments are observations, interviews and documentation.  The study found that the foster pattern Granny used to her grandson was as follows: The permissive foster pattern, Grandma gives the grandson freedom to set himself up. Grandma did not give much control to her grandson but even so in decision making that concerns the interests of grandmothers still involve grandchildren, Grandma also does not use physical punishment if grandchildren make mistakes. The nature of this foster pattern is that there is no binding rule on the grandchild, what the grandchild is allowed grandmother. Foster democracy pattern, in this foster pattern Grandma does not apply rules that are forcing grandchildren to behave in accordance with the desired grandmother but even though grandchildren are not given the rule of grandchildren should know when the meal time and when the time should be To play. There is an attitude like mutual respect and exchanging between grandma and grandchild is important because it can form mutual respect for each other and the creation of a warm relationship between grandma and grandchild. Mixed parenting, Grandma always supports the desire and willingness of grandchildren but sometimes grandmother also gave the rule to grandchildren. As well as grandma trying to advise first but if the grandchild does not listen to her new advice he uses violence to the physical grandchildren such as the ears of grandchildren so that grandchildren can be deterrent with his deeds.  Keywords: Foster Pattern, Family, Children.